2020
DOI: 10.1002/jsfa.10464
|View full text |Cite
|
Sign up to set email alerts
|

Ionic strength and pH stability of oil‐in‐water emulsions prepared with acid‐hydrolyzed insoluble proteins from Chlorella protothecoides

Abstract: BACKGROUNDChlorella protothecoides is one of the most widely commercialized and studied microalgae species. Recent research reported improved emulsifying properties of the insoluble protein fraction from C. protothecoides after thermal–acid treatment.RESULTSIn this research, we studied the influence of ionic strength (sodium chloride 50–500 mmol L−1 or calcium chloride 5–50 m mol L−1) and pH (2–9) on the stability of oil‐in‐water emulsions prepared by 3% (w/w) of the untreated insoluble microalgae protein frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Dai et al studied the influence of ionic strength on the stability of emulsions and reported that the bridging mechanism is not electrostatically driven and is rather due to Van der Waals interactions. 14,17 Knudsen et al, 31 similarly, reported an increase in the viscosity of emulsions stabilized by heat-induced ⊎-lactoglobulin aggregates as a result of stronger interactions between adsorbed molecules at the oilwater interface due to the presence of aggregates with higher surface hydrophobicity. Aside from bridging, entanglement may also play a role.…”
Section: Influence Of Oil Content and Protein Fraction Type On Emulsion Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al studied the influence of ionic strength on the stability of emulsions and reported that the bridging mechanism is not electrostatically driven and is rather due to Van der Waals interactions. 14,17 Knudsen et al, 31 similarly, reported an increase in the viscosity of emulsions stabilized by heat-induced ⊎-lactoglobulin aggregates as a result of stronger interactions between adsorbed molecules at the oilwater interface due to the presence of aggregates with higher surface hydrophobicity. Aside from bridging, entanglement may also play a role.…”
Section: Influence Of Oil Content and Protein Fraction Type On Emulsion Characteristicsmentioning
confidence: 99%
“…[14][15][16][17] Results from investigations of the behavior of moderately concentrated oil-in-water emulsion (with 10% w/w of a mediumchain triglycerides oil) stabilized by the microalgae insoluble protein fraction after hydrolyzing with 0.5 mol L -1 HCl at 85°C for 4 h (Hydrolysates 85) showed that emulsions were stable in terms of droplet size (at around 15 μm) after 14 days of storage, even when subjected to harsh environmental conditions such as an extreme pH (2)(3)(4)(5)(6)(7)(8)(9) or high salt concentrations (NaCl concentration 0-500 mmol L -1 or CaCl 2 concentration 0-50 mmol L -1 ), and no coalescence was observed. 14,17 However, visual and microscopic assessments revealed pronounced emulsion flocculation. In emulsions with low oil droplet concentrations, flocculation caused emulsion instability by accelerating gravitational separation due to the larger effective droplet size compared with individual emulsion droplets.…”
Section: Introductionmentioning
confidence: 99%